Critical Analysis of Health Workers’ Roles in Digital Healthcare Transformation - Almarhoon, Alyah Ali; Alturaiki, Fatimah Ibrahim Ali; Al-Sultan, Khalid Hamad; AlAli, Fatima Ali Taher; Algheryafi, Zahraa Ali; Al seeaid, Ebtisam Abdullah Ahmed; Al Ali, Badrya Taher; Alshammar, Norah Fahad; Alhashim, Fatimah Mohammad; Alhashim, Jalila Mohammad (Journal of Ecohumanism, 2024)
Modern, highly developed health care systems coupled with drastic advancements in information technology have led to changes in the responsibilities of health workers. This paper aims to addresses Cutting edge topic and reviewed the new frontier of internet accessible and healthcare implication to the work force. The paper also investigates factors concerning the strengths and weaknesses of these new systems for health worker training, working satisfaction, and patient care results. Some major points noted include promotion of technology skills, e-Health records, telehealth and Artificial intelligence built to improve consumer satisfaction. The paper offers the recommendations needed to enable easy coping by health workers in the digital healthcare environment.